An efficient and facile method to develop defect-free OLED displays. (27th April 2021) - Solanki, Ankur; Awasthi, Asha; Unni, K N Narayanan; Deepak
Abstract: Organic light emitting diodes (OLEDs) have captured the attention of the flat-panel display market owing to their high luminescence and versatile properties. However, substrate processing plays a critical part in the fabrication of OLED displays, demonstrated here as a passive matrix display, where plenty of defects, which appear during the processing stage, result in poor display quality and yield. Photolithography is the most common technique used to develop the electrode pattern on a transparent glass substrate. Nevertheless, poor lithography leads to display defects such as dead pixels, dark columns and bright horizontal rows. Moreover, shorts between anodes due to partial etching of the transparent conducting material or cathode lines are also common problems. Herein, we discuss a technique which drastically reduces the number of electrode shorts. Selective etching of the cathode in this technique makes the optical inspection of electrode shorts far easier due to the higher contrast ratio between Cr/glass compared to indium tin oxide/glass. Further, a focused laser beam is employed to ablate the identified shorts between two or more anode/cathode lines to make the short-free patterns. Additionally, a laser beam is also capable of isolating the burnt/dead pixels in a display, which otherwise lead to dark or bright lines during operation. Thus, our findings are very important for the display industry to develop defect-free panels and for the repair of certain operational defects to increase the production yield and lifetime.